Nonbank Lending and Credit Cyclicality - Fleckenstein, Quirin; Gopal, Manasa; Gutiérrez, Germán; Hillenbrand, Sebastian (Review of Financial Studies, 2026)
Abstract We study the contribution of banks and nonbanks to cyclical fluctuations in the supply of syndicated loans. We find that a reduction in nonbank lending explains most of the contraction in syndicated credit and the associated employment losses during the Global Financial Crisis, while banks’ contribution is small. Looking over multiple cycles, we find nonbanks’ credit supply is roughly three times as cyclical as banks’, suggesting that nonbanks are the main drivers of syndicated lending cycles. A model in which government support stabilizes bank funding can explain the higher cyclicality of nonbanks.